2018
DOI: 10.7189/jogh.08.020418
|View full text |Cite
|
Sign up to set email alerts
|

Improving Community Health Worker performance by using a personalised feedback dashboard for supervision: a randomised controlled trial

Abstract: BackgroundCountries across sub-Saharan Africa are scaling up Community Health Worker (CHW) programmes, yet there remains little high-quality research assessing strategies for CHW supervision and performance improvement. This randomised controlled trial aimed to determine the effect of a personalised performance dashboard used as a supervision tool on the quantity, speed, and quality of CHW care.MethodsWe conducted a randomised controlled trial in a large health catchment area in peri-urban Mali. One hundred fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 24 publications
0
53
0
2
Order By: Relevance
“…Research has played a fundamental role; Medic Mobile staff and our partners have produced more than thirty peer-reviewed publications. Study methods have ranged from ethnography (Holeman & Barrett, 2017 ) to randomized controlled trials (Whidden et al, 2018 ), and design research methods including research through design (Zimmerman, Forlizzi, & Evenson, 2007 ) and action design research (Sein et al, 2011 ). While each of these studies answered questions about specific design projects, over time we came to see that this collection of articles did not amount to an accessible, substantive reflection on our design practice as a whole – a gap we hoped to address through this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Research has played a fundamental role; Medic Mobile staff and our partners have produced more than thirty peer-reviewed publications. Study methods have ranged from ethnography (Holeman & Barrett, 2017 ) to randomized controlled trials (Whidden et al, 2018 ), and design research methods including research through design (Zimmerman, Forlizzi, & Evenson, 2007 ) and action design research (Sein et al, 2011 ). While each of these studies answered questions about specific design projects, over time we came to see that this collection of articles did not amount to an accessible, substantive reflection on our design practice as a whole – a gap we hoped to address through this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Different approaches to supervision and support to community health workers have been tried. There is no consensus regarding who should provide the supervision, where it should be done, at what frequency, with what content, and with what tools [ 13 ]. Supervision approaches should be context-specific [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, results from a study in Ghana show that the effects of supervision on CHW productivity depend on how supportive the supervisors were [ 17 ]. Another study from Mali found that dedicated monthly supervision with feedback tailored to each CHW was associated with gains in CHW productivity [ 34 ].…”
Section: Introductionmentioning
confidence: 99%